2000
DOI: 10.1074/jbc.m001780200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Human Neutrophils by Chemotactic Factors Is Associated with the Activation of Phosphatidylinositol 3-Kinase γ

Abstract: The activation of human polymorphonuclear neutrophil leukocytes (neutrophils) is associated with an increased synthesis of the highly phosphorylated phosphatidylinositol 3,4,5-trisphosphate (PtdIns(3,4,5)P 3 ). The aims of the present investigation were to determine whether the newly described, G protein-dependent phosphatidylinositol 3-kinase (PI3K), p110␥, was involved in the responses to chemotactic factors interacting with G protein-coupled receptors. The presence of p110␥ in neutrophils was first establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 53 publications
5
50
1
Order By: Relevance
“…5). Because many studies have shown that PI3K is activated after PMN stimulation (39,53,54), our results suggest that this activation results in the delivery of a negative signal, which counters positive regulatory pathways in the regulation of the rate of PMN migration. Protein tyrosine phosphorylation/dephosphorylation, on the other hand, serves as a downstream signal that most likely occurs after fMLP stimulation and CD47 translocation.…”
Section: Discussionmentioning
confidence: 78%
“…5). Because many studies have shown that PI3K is activated after PMN stimulation (39,53,54), our results suggest that this activation results in the delivery of a negative signal, which counters positive regulatory pathways in the regulation of the rate of PMN migration. Protein tyrosine phosphorylation/dephosphorylation, on the other hand, serves as a downstream signal that most likely occurs after fMLP stimulation and CD47 translocation.…”
Section: Discussionmentioning
confidence: 78%
“…Upon binding the chemokine, the activated receptor releases the Gβγ heterodimer from associated trimeric G-proteins, which can then promote the activation of phosphatidylinositol 3-kinase-γ (PI3Kγ), the production of phosphatidylinositol 3,4,5 trisphosphate and the activation of protein kinase B (akt/PKB). Activation of this signaling cascade is thought to play a pivotal role during both human and mouse neutrophil migration by stimulating F-actin polymerization [29][30][31][32]. However, the lack of PI3Kγ in knockout mice does not appear to affect random neutrophil migration, even in the presence of a chemoattractant (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membranes were isolated as previously described (27,28). Briefly, neutrophils (40 ϫ 10 6 cells/ml) were incubated with 1 mM DFP for 30 min at room temperature, washed, and kept for 5 min at 37°C before stimulation with 3 mg/ml MSU crystals.…”
Section: Isolation Of Plasma Membranesmentioning
confidence: 99%